DETERMINAN PENGELUARAN KESEHATAN DI ASEAN: STUDI KASUS TAHUN 2012- 2021 - Hendra Prasetya; Winny Perwithosuci (JURNAL ILMIAH EDUNOMIKA, 2025)
Healthcare spending in ASEAN countries has been increasing along with economic growth, changes in the aging population, and urbanization. The growing number of elderly people and differences in mortality rates across countries create challenges in healthcare financing. This study aims to understand how economic growth, the elderly population, the labor force, and mortality rates affect healthcare spending in 10 ASEAN countries from 2012 to 2021. To analyze these relationships, the study uses statistical methods that compare different models for more accurate results. The findings show that higher economic growth and a larger elderly population lead to increased healthcare spending. Meanwhile, the effect of mortality rates on healthcare spending varies depending on the quality of healthcare infrastructure in each country. Additionally, urbanization also plays a role in driving healthcare spending. It is hoped that this research can help the government in determining policies in the health system in each country.